International Research Laboratories in Russia: Factors Underlying Scientists’ Satisfaction with Their Work - Ronald Inglehart; Tatiana Karabchuk; Stanislav Moiseev; Marina Nikitina (Foresight and STI Governance, 2013)
International research laboratories represent a relatively new form for Russia of organizing the scientific community. They aim to attract leading international scientists as well as young scholars and thus to help increase national research capabilities. This paper analyses the efficiency of international labs in achieving these goals in terms of criteria that are intrinsic (number of publications, patents etc.) and perceived (job satisfaction). Motivation and involvement of employees as well as availability of resources are regarded as the main determinants of efficiency. Based on previous international and domestic studies in the field we build a conceptual model to estimate causal relations and correlations between these five variables.  Our data source was the online survey of international scientific laboratories staff, which was conducted in April-June, 2012.